Polymer and preparation method thereof, binder, diaphragm, manganese-based lithium battery and vehicle

By using polymers with a three-dimensional grid structure and rich functional group sites in the lithium battery separator, the problem of transition metal ions migration in the lithium battery is solved, and the performance and safety of manganese-based lithium batteries are improved.

CN119241739APending Publication Date: 2025-01-03CHONGQING CHANGAN AUTOMOBILE CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411374773.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

During the charging and discharging process of lithium battery positive electrode materials containing transition metals, they easily cause the dissolution of transition metal ions, which passes through the diaphragm to migrate to the negative electrode, destroys the solid electrolyte interface, affects the circulation performance and safety of lithium batteries, and the existing diaphragm capture capability is insufficient. It is difficult to effectively solve this problem.

Method used

Using a polymer that includes a backbone polymer and a first branch, the backbone polymer has a three-dimensional grid structure and rich functional group sites, which can be captured with transition metal ions by chelation coordination to enhance the separator's Adhesion effect and mechanical strength, and improve water solubility and ion transport capability through active groups.

Benefits of technology

It significantly improves the rate performance, cycle life and safety of manganese-based lithium batteries, reduces the risk of transition metal ions migration, enhances the thermal stability and lithium ion transmission efficiency of the diaphragm, avoids dendrites and internal short circuits, and improves The overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241739A_ABST
    Figure CN119241739A_ABST
Patent Text Reader

Abstract

The invention relates to a polymer and a preparation method thereof, a binder, a diaphragm, a manganese-based lithium battery and a vehicle, and relates to the field of lithium batteries. The polymer comprises a main chain polymer and a first branch chain, the main chain polymer comprises a structural unit shown in the formula I, the first branch chain comprises a chelating agent and # imgabs0, and Y in the formula I represents the bonding position of the main chain polymer and the first branch chain. Therefore, the binder comprising the polymer has excellent transition metal ion capturing ability, bonding effect and mechanical strength, and the corresponding diaphragm has excellent transition metal ion capturing ability, bonding effect and thermal stability, so that the rate capability, cycle life and safety of the manganese-based lithium battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a polymer and a preparation method thereof, a binder, a diaphragm, a manganese-based lithium battery and a vehicle. Background Art

[0002] Lithium batteries have the advantages of high energy density, long cycle life, and no memory effect, and are widely used in consumer electronics, energy storage, electric vehicles, etc. Lithium batteries include positive electrodes, negative electrodes, electrolytes, and separators. The separator is located in the electrolyte between the positive and negative electrodes. The separator can be used to separate the positive and negative electrodes to prevent short circuits in lithium batteries, and can also be used to provide a channel for lithium ion transmission.

[0003] Positive electrode materials containing transition metals have the advantages of low cost, high voltage platform, high energy density, safe and stable material structure, etc., so they are widely used in lithium batteries. However, positive electrode materials containing transition metals are prone to the problem of transition metal ion dissolution during the charging and discharging process. The diaphragm usually has no ability to capture transition metal ions or has a weak ability to capture transition metal ions. Transition metal ions may migrate through the diaphragm to the negative electrode surface of the lithium battery and deposit. This will not only destroy the solid electrolyte interface membrane and affect the cycle performance and storage performance of the lithium battery, but in severe cases, it may even form dendrites that pierce the diaphragm and cause an internal short circuit in the lithium battery, thereby causing safety problems. Summary of the invention

[0004] The present application provides a polymer and a preparation method thereof, a binder, a diaphragm, a manganese-based lithium battery and a vehicle. Thus, the binder including the polymer has excellent transition metal ion capture ability, bonding effect and mechanical strength, which is conducive to improving the rate performance, cycle life and safety of the manganese-based lithium battery.

[0005] The technical solution of this application is as follows:

[0006] According to the first aspect of the present application, a polymer is provided, the polymer comprising a main chain polymer and a first branch chain, the main chain polymer comprising a structural unit shown in Formula I, the first branch chain comprising a chelating agent,

[0007]

[0008] Wherein, Y in Formula I represents the bonding position between the main chain polymer and the first branch chain.

[0009] According to the above technical means, in the polymer, the chelating agent in the first branch chain can chelate and coordinate with the transition metal ions (such as manganese ions), thereby achieving the capture of transition metal ions (such as manganese ions). The main chain polymer with a three-dimensional grid structure has abundant functional group sites, which can increase the number of first branches on the polymer, and then increase the number of chelating agents on the polymer, which is beneficial to improve the capture effect of the polymer on transition metal ions, and can greatly reduce the transfer of transition metal ions to the negative electrode of the lithium battery, making the solid electrolyte interface film not easily destroyed, the cycle performance and storage performance of the lithium battery are better, and the probability of lithium battery safety problems is reduced.

[0010] The structure of the main chain polymer is a three-dimensional structure formed by the interweaving of intramolecular or intermolecular hydrogen bonds. The hydrogen bonds in the main chain polymer can be firmly connected to the bonded material (such as inorganic particles). The three-dimensional structure in the main chain polymer can greatly increase the sites of firm connection. The interaction of multi-dimensional hydrogen bonds in the main chain polymer makes it easier to achieve the connection between the polymer and the bonded material (such as inorganic particles), thereby improving the bonding effect of the polymer.

[0011] When the binder in the diaphragm includes the above-mentioned polymer, the polymer is not prone to chain slip, and the chelating agent in the binder can reversely increase the stability and mechanical strength of the binder by chelating and coordinating with transition metal ions, and effectively protect the bonded materials (such as inorganic particles in the diaphragm) from falling off. In this way, the thermal stability of the diaphragm is relatively high, so that the lithium battery has a lower safety risk during high-temperature cycling.

[0012] In a possible embodiment, the polymer includes a second branch chain, the second branch chain includes an active group, and the active group is used to increase the steric hindrance of the polymer. The main chain polymer includes a first main chain polymer, and the first main chain polymer includes a structural unit shown in Formula II.

[0013]

[0014] Wherein, R in Formula II represents the bonding position between the first main chain polymer and the second branch chain.

[0015] According to the above technical means, the second branch chain in the polymer includes an active group, which is used to increase the steric hindrance of the polymer, reduce the crystallinity of the polymer (increase the disorder of the polymer), and then improve the water solubility of the polymer, while the first main chain polymer itself has an excellent bonding effect (the main chain polymer exhibits an excellent bonding effect through hydrogen bonds between molecules and within molecules). In this way, a water-soluble polymer with excellent bonding effect can be obtained, and a water-soluble binder with excellent bonding effect can also be obtained. When the binder in the diaphragm includes the above polymer, the water-soluble binder with excellent bonding effect can better bond the bonded material (such as inorganic particles or base film in the diaphragm), which is beneficial to improve the thermal stability of the diaphragm, so that the lithium battery has a lower safety risk during high-temperature cycling.

[0016] Furthermore, since the first main chain polymer has abundant functional group sites, the number of second branches on the polymer can be increased, which is beneficial to increase the number of active groups on the polymer, further improve the water solubility and bonding effect of the binder, and help further improve the thermal stability of the diaphragm and improve the safety of lithium batteries during high-temperature cycling.

[0017] In a possible embodiment, the polymer includes a plurality of different first branches, the main chain polymer includes a second main chain polymer, and the second main chain polymer includes a structural unit shown in Formula III,

[0018]

[0019] Wherein, Y1, Y2, and Y3 in Formula III represent the bonding positions between the second main chain polymer and a plurality of different first side chains.

[0020] According to the above technical means, different first side chains can be introduced into the polymer according to actual needs, so that the polymer has better manganese ion capture ability.

[0021] In a possible embodiment, the polymer includes a plurality of different second branches, the main chain polymer includes a third main chain polymer, and the third main chain polymer includes a structural unit shown in Formula IV,

[0022]

[0023] Wherein, R1, R2, and R3 in Formula IV represent the bonding positions of the third main chain polymer and the plurality of different second side chains.

[0024] According to the above technical means, different second side chains can be introduced into the polymer according to actual needs, so as to obtain a water-soluble polymer with excellent bonding effect, and then obtain a water-soluble adhesive with excellent bonding effect.

[0025] In one possible embodiment, the chelating agent comprises

[0026] At least one of .

[0027] According to the above technical means, the binder can be fully extended on the bonded material (such as the base film in the diaphragm), and each chelating agent can include multiple complexing sites. The multiple complexing sites can be multi-dentately coordinated and chelated with the transition metal ions in the electrolyte to form an inner orbital hybrid chelate, which has good stability and is not prone to dissociation. In this way, when the binder in the diaphragm includes the above polymer, the diaphragm has an excellent effect of capturing transition metal ions, which can reduce the transfer of transition metal ions to the negative electrode of the lithium battery, the solid electrolyte interface membrane is not easily destroyed, the cycle performance and storage performance of the lithium battery are better, and it can also effectively prevent dendrites from piercing the diaphragm to cause internal short circuit of the battery, thereby reducing the probability of battery safety problems.

[0028] In one possible embodiment, the active group includes

[0029] At least one of .

[0030] According to the above technical means, the active groups of the above structure can increase the steric hindrance of the polymer, improve the disorder of the polymer, and then improve the water solubility of the polymer to obtain a water-soluble polymer with excellent bonding effect. When the binder in the diaphragm includes the above polymer, the water-soluble binder with excellent bonding effect can effectively protect the bonded material (such as inorganic particles in the diaphragm) from falling off. In this way, the thermal stability of the diaphragm is relatively high, so that the lithium battery has a lower safety risk during high-temperature cycling.

[0031] In one possible embodiment, the active group includes At least one of .

[0032] According to the above technical means, the second branch in the polymer includes an active group, and the active group can also include a functional group for transmitting lithium ions, which can significantly improve the lithium ion transmission effect of the polymer. The main chain polymer can also form a three-dimensional transmission channel, which can greatly improve the transmission rate of lithium ion transmission. When the binder in the diaphragm includes the above polymer, the binder has an excellent ion transmission effect, which is beneficial to improving the rate performance of the lithium battery. In addition, since the main chain polymer has abundant functional group sites, the number of second branches on the polymer can be increased, which is beneficial to increase the number of active groups on the polymer, further improve the ion transmission effect of the binder, and improve the rate performance of the lithium battery.

[0033] Furthermore, since the polymer modified by the second branch chain has stronger hydrophilicity, in addition, the polymer with a three-dimensional network structure has abundant polar groups (carboxyl, hydroxyl, etc.), which can form multidimensional hydrogen bonds with the electrolyte solvent, and can attract more electrolyte into the polymer with a three-dimensional network structure, so that the polymer has certain swelling properties. When the binder in the diaphragm includes the above polymer, the binder has the capacity to accommodate the electrolyte, which can further improve the ion transmission effect of the diaphragm and improve the rate performance of the lithium battery.

[0034] In a possible embodiment, the polymer further includes a polar group (such as a hydroxyl group), and the polar group is bonded to the main chain polymer.

[0035] According to the above technical means, polar groups (such as hydroxyl groups) can further increase the bonding effect of the polymer.

[0036] In one possible embodiment, the number of repetitions of the structural unit represented by Formula I of the main chain polymer is 15 to 300.

[0037] According to the above technical means, the average molecular weight of the polymer is moderate, and the polymer has better bonding effect and mechanical properties.

[0038] In one possible embodiment, the number of repetitions of the structural unit represented by Formula II of the main chain polymer is 15 to 300.

[0039] In one possible embodiment, the number of repetitions of the structural unit represented by formula III of the main chain polymer is 5 to 100.

[0040] In one possible embodiment, the number of repetitions of the structural unit represented by Formula IV of the main chain polymer is 5 to 100.

[0041] In one possible implementation, the weight average molecular weight of the polymer is 400,000 to 1,000,000.

[0042] According to the above technical means, the problem that the weight average molecular weight of the polymer is too low, resulting in low mechanical strength of the polymer and easy deformation of the corresponding diaphragm, can be alleviated. The problem that the weight average molecular weight of the polymer is too high, resulting in poor bonding effect of the polymer can also be alleviated.

[0043] According to a second aspect provided by the present application, a method for preparing the polymer described in the above embodiment is provided, comprising: subjecting a first polymer, an amidation agent, and a chelating agent to an amidation reaction in an aqueous solvent to obtain a polymer; wherein the first polymer comprises a structural unit as shown in the following formula V,

[0044]

[0045] In some possible embodiments, the first polymer includes chitosan.

[0046] In a possible embodiment, before the amidation reaction, the first polymer and the alkylating agent are subjected to an alkylation reaction. For example, the alkylating agent includes the above-mentioned active group having an alkyl group.

[0047] In a possible embodiment, before the amidation reaction, the first polymer and the carboxylation agent are subjected to a carboxylation reaction. For example, the carboxylation agent includes the above-mentioned active group having a carboxyl group.

[0048] According to a third aspect provided by the present application, a binder is provided, and the binder includes the polymer of the above-mentioned first aspect and any possible embodiment thereof.

[0049] According to a fourth aspect provided by the present application, a diaphragm is provided, the diaphragm comprising a base film and a film layer arranged on at least one surface of the base film, the film layer comprising inorganic particles and the binder of the above second aspect.

[0050] In a possible implementation, the mass fraction of the binder in the separator is 0.01% to 10%.

[0051] According to the fifth aspect provided by the present application, a manganese-based lithium battery is provided, and the manganese-based lithium battery includes the diaphragm of the fourth aspect and any possible implementation manner thereof.

[0052] According to the sixth aspect provided by the present application, there is provided an electrical device, the electrical device comprising the manganese-based lithium battery of the fifth aspect.

[0053] Therefore, the above technical features of the present application have the following beneficial effects:

[0054] (1) Excellent Mn 2+ Capture efficiency.

[0055] In the polymer, the chelating agent in the first branch can chelate and coordinate with transition metal ions (such as manganese ions), thereby achieving the capture of transition metal ions (such as manganese ions). The main chain polymer with a three-dimensional grid structure has abundant functional group sites, which can increase the number of first branches on the polymer, and then increase the number of chelating agents on the polymer, which is beneficial to improve the polymer's capture effect on transition metal ions, and can greatly reduce the transfer of transition metal ions to the negative electrode of the lithium battery. The solid electrolyte interface film is not easily destroyed, the lithium battery has better cycle performance and storage performance, and the probability of lithium battery safety problems is reduced.

[0056] When the binder in the diaphragm includes the above-mentioned polymer, the binder can be fully extended on the bonded material (such as the base film in the diaphragm), and the chelating agent in the binder can include multiple complexing sites. The multiple complexing sites can undergo multi-dentate coordination and chelation with the transition metal ions in the electrolyte to form an inner orbital hybrid chelate. The chelate has good stability and is not prone to dissociation, which is further beneficial to improving the binder's capture effect on transition metal ions.

[0057] (2) Excellent water-soluble bonding effect.

[0058] The second branch in the polymer includes an active group, which is used to increase the steric hindrance of the polymer, improve the disorder of the polymer, and further improve the water solubility of the polymer. The main chain polymer itself has an excellent bonding effect, so a water-soluble polymer with excellent bonding effect can be obtained, and a water-soluble adhesive with excellent bonding effect can also be obtained. Since the main chain polymer has abundant functional group sites, the number of the second branch on the polymer can be increased, which is conducive to increasing the number of active groups on the polymer and further improving the bonding effect of the water-soluble adhesive.

[0059] Furthermore, the hydrogen bonds in the polymer can be firmly connected to the bonded material (such as inorganic particles), and the three-dimensional structure in the main chain polymer can greatly increase the firmly connected sites. The interaction of the multi-dimensional hydrogen bonds in the main chain polymer makes it easier to achieve the connection between the polymer and the bonded material (such as inorganic particles), thereby improving the bonding effect of the water-soluble polymer. In addition, the main chain polymer on the polymer also includes polar groups, which is conducive to improving the bonding effect of the polymer. In summary, the bonding effect of the water-soluble binder including the polymer can be further improved.

[0060] (3) Excellent ion transmission effect.

[0061] The second branch in the polymer includes an active group, and the active group may also include a functional group for transmitting lithium ions, which can significantly improve the lithium ion transmission effect of the polymer. The main chain polymer can also form a three-dimensional transmission channel, which can greatly improve the transmission rate of lithium ion transmission. When the binder in the diaphragm includes the above polymer, the binder has an excellent ion transmission effect, which is beneficial to improving the rate performance of the lithium battery. In addition, since the main chain polymer has abundant functional group sites, the number of second branches on the polymer can be increased, which is beneficial to increase the number of active groups on the polymer, further improve the ion transmission effect of the binder, and improve the rate performance of the lithium battery.

[0062] Furthermore, since the polymer modified by the second branch chain has stronger hydrophilicity, in addition, the polymer with a three-dimensional network structure has abundant polar groups (carboxyl, hydroxyl, etc.), which can form multidimensional hydrogen bonds with the electrolyte solvent, and can attract more electrolyte into the polymer with a three-dimensional network structure, so that the polymer has certain swelling properties. When the binder in the diaphragm includes the above polymer, the binder has the capacity to accommodate the electrolyte, which can further improve the ion transmission effect of the binder and improve the rate performance of the lithium battery.

[0063] (4) Excellent mechanical strength.

[0064] When the binder in the diaphragm includes the above-mentioned polymer, the polymer is not prone to chain slip, and the chelating agent in the binder can reversely increase the stability and mechanical strength of the binder by chelating and coordinating with transition metal ions, and effectively protect the bonded materials (such as inorganic particles in the diaphragm) from falling off. In this way, the thermal stability of the diaphragm is relatively high, so that the lithium battery has a lower safety risk during high-temperature cycling.

[0065] (5) Good prospects for large-scale application.

[0066] Compared with non-water-soluble binders, the binder provided in the present application can effectively avoid the use of organic toxic solvents, and has abundant sources. It can replace the binder in the existing lithium battery system for use, has good prospects for large-scale application, and is conducive to solving the problem that a single complexing agent is introduced into the lithium battery system, has a large size, has low complexing efficiency, and is easy to affect the performance of the lithium battery.

[0067] In addition, the binder provided by the present application has excellent Mn 2+ Capture efficiency, excellent ion transmission effect, excellent mechanical strength, and the corresponding lithium batteries have excellent rate performance, cycle life and safety, which are further conducive to improving the prospects for large-scale application of binders.

[0068] It should be noted that the technical effects brought about by any implementation method in the second to sixth aspects can refer to the technical effects brought about by the corresponding implementation method in the first aspect, and will not be repeated here.

[0069] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] The drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present application, and together with the specification are used to explain the principles of the present application, and do not constitute an improper limitation on the present application.

[0071] Figure 1 is a schematic diagram of a chelate formed by complexing a polymer and a manganese ion according to an exemplary embodiment;

[0072] Figure 2 is another schematic diagram of a chelate formed by complexing a polymer and a manganese ion according to an exemplary embodiment;

[0073] Figure 3 is a schematic structural diagram of a diaphragm according to an exemplary embodiment;

[0074] Figure 4 yes Figure 3 Schematic diagram of the structure for bonding inorganic particles and binder in a coating material. DETAILED DESCRIPTION

[0075] In order to enable ordinary persons in the art to better understand the technical solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings.

[0076] In the specification and claims of the present application, the terms "first", "second", etc. are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable where appropriate, so that the embodiments of the present application described here can be implemented in an order other than those illustrated or described here. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present application. On the contrary, they are only examples of devices and methods consistent with some aspects of the present application as detailed in the attached claims.

[0077] Electric vehicles are a new energy vehicle with advantages such as environmental protection, energy saving and low operating costs. Batteries play a vital role in electric vehicles. Batteries are the power source of electric vehicles and are directly related to the range, charging time and efficiency of electric vehicles. Among them, lithium batteries have the advantages of high energy density, long cycle life and no memory effect, and are widely used in consumer electronics, energy storage, electric vehicles and other fields.

[0078] Lithium batteries mainly include positive electrode, electrolyte, negative electrode and separator.

[0079] The positive electrode of a lithium battery includes a positive electrode material, which is usually a lithium-containing compound. The lithium-containing compound can be used to provide a lithium source, store and release lithium ions, and the transition metal ions in the lithium-containing compound will gain and lose electrons during the charge and discharge process to undergo redox reactions to release electrical energy. Among them, positive electrode materials containing transition metals have the advantages of low cost, high voltage platform, high energy density, and safer and more stable material structure, so they are widely used in lithium batteries. The electrolyte in the lithium ion includes lithium salts and organic solvents, and the electrolyte can be used to achieve the lithium ion conduction effect between the positive electrode and the negative electrode. The negative electrode in a lithium battery includes a negative electrode material, and the negative electrode material of the lithium battery can be used to reversibly extract and embed lithium ions to store and release energy.

[0080] The separator in the lithium battery includes a substrate layer and a coating layer. The substrate layer includes a base film, and the coating layer includes a binder and inorganic particles. The separator is located in the electrolyte between the positive electrode and the negative electrode. It can be used to separate the positive and negative electrodes of the lithium battery to prevent the lithium battery from short circuiting, and can also be used to provide a channel for lithium ion transmission.

[0081] The positive electrode materials containing transition metals are prone to the problem of transition metal ion precipitation during the charge and discharge process. The diaphragm usually has no ability to capture transition metal ions or has a weak ability to capture transition metal ions. Transition metal ions may migrate to the negative electrode surface of the lithium battery and deposit (for example, the positive electrode materials containing manganese are prone to manganese ions (Mn 2+ ) dissolution phenomenon (John-Teller effect), manganese ions (Mn 2+ ) may migrate through the diaphragm to the negative electrode for deposition), which will not only destroy the solid electrolyte interface (SEI film) and affect the cycle performance and storage performance of the lithium battery, but in severe cases may even form dendrites that pierce the diaphragm and cause an internal short circuit in the lithium battery, thus causing safety problems.

[0082] In some cases, a separator with an amino group can inhibit the migration of transition metal ions to the negative electrode side. For example, a separator with an amino group will coordinate and complex with transition metal ions in the electrolyte to achieve the capture of transition metal ions in the electrolyte, but this solution includes at least the following problems: (1) Due to the small number of functional group sites on the separator and the small number of amino groups on the separator, the capture effect of transition metal ions by the separator is poor; (2) Due to the low complexing efficiency of a single complexing functional group (amino group), the stability of the formed complex is poor, the complex is easy to dissociate, and the transition metal ions generated by the dissociation will return to the electrolyte. In other cases, metal chelate powder can be added to the separator to capture transition metal ions through the metal chelate in the separator to inhibit the migration of transition metal ions to the negative electrode side. For example, in the process of preparing the diaphragm, a powder of tetralithium ethylenediaminetetraacetic acid is added to achieve the capture of transition metal ions in the electrolyte. However, this solution includes at least the following problems: (1) The tetralithium ethylenediaminetetraacetic acid is introduced into the diaphragm in the form of a powder. Therefore, the tetralithium ethylenediaminetetraacetic acid may be unevenly distributed in the diaphragm, which is not conducive to the capture of transition metal ions; (2) The addition of tetralithium ethylenediaminetetraacetic acid may lead to an increase in the number of ionic insulators, increase the system impedance, and affect the cycle life of the lithium battery.

[0083] Based on this, the embodiment of the present application proposes a vehicle, which can be a pure electric vehicle or a hybrid electric vehicle. In order to realize the basic functions of the vehicle, the vehicle may include a body, a chassis, a battery system and a power system. Of course, the vehicle may also include other components, which are only illustrative here and do not limit the specific composition of the vehicle.

[0084] The vehicle body may include a vehicle frame, vehicle doors and vehicle windows. The vehicle frame may form the overall shape of the exterior of the vehicle and form a seating space for accommodating passengers. The vehicle doors may be rotatably connected to the vehicle frame and may open or close the interior passenger space. The vehicle windows may be mounted on the vehicle doors or the vehicle frame to facilitate passengers to observe the external environment. The chassis may include components such as a transmission system and a drive system. Among them, the drive system may drive the wheels to rotate. Depending on the driving mode of the drive system, the drive system may be divided into front-wheel drive, rear-wheel drive and four-wheel drive arrangements. The transmission system may transmit the power generated by the power system to the wheels. The power system may provide power to the vehicle so that the vehicle can complete basic driving functions. Depending on the type of vehicle, the composition of the power system may also be different. Exemplarily, when the vehicle is an electric vehicle, the power system may include an electric motor.

[0085] In order to power a power system (such as an electric motor), the vehicle provided in the embodiment of the present application also includes a battery system, and the battery system includes a lithium battery, which can be used to provide electrical energy. The lithium battery can be electrically connected to the power system of the vehicle, so that the electrical energy of the battery pack can be transferred to the power system of the vehicle for powering. The lithium battery can be a liquid lithium battery or a semi-solid lithium battery.

[0086] From the above analysis, it can be seen that the ability of the diaphragm to capture transition metal ions is poor, and the transition metal ions may migrate to the negative electrode surface of the lithium battery and deposit, affecting the battery's cycle performance, storage performance and safety performance. Based on this, in order to improve the ability of the diaphragm to capture transition metal ions, the diaphragm provided in the embodiments of the present application includes a polymer.

[0087] In some embodiments, the polymer includes a main chain polymer and a first branch chain, the main chain polymer includes a structural unit shown in Formula I, the first branch chain includes a chelating agent,

[0088]

[0089] Wherein, Y in Formula I represents the bonding position between the main chain polymer and the first branch chain.

[0090] like Figure 1 and Figure 2 As shown, the first branch chain includes a chelating agent (such as a tertiary amino group and a hydroxyl group) to capture transition metal ions (such as Mn 2+ ) process, the chelating agent in the first branch can react with transition metal ions (such as Mn 2+ ) to form chelates, thereby achieving the transition metal ions (such as Mn 2+ ) capture. Compared with the main chain polymer with a straight chain structure, the main chain polymer with a three-dimensional grid structure has abundant functional group sites. The abundant functional group sites can increase the number of the first branch on the polymer, thereby increasing the number of chelating agents on the polymer, which is beneficial to improving the polymer's capture effect on transition metal ions, and can greatly reduce the transfer of transition metal ions to the negative electrode of the lithium battery. The solid electrolyte interface film is not easily destroyed, the cycle performance and storage performance of the lithium battery are better, and the probability of lithium battery safety problems is reduced.

[0091] like Figure 1 As shown, the structure of the main chain polymer is a three-dimensional structure formed by the interweaving of intramolecular or intermolecular hydrogen bonds (in this three-dimensional structure, the hydrogen bonds show multi-dimensional interactions). The hydrogen bonds in the main chain polymer can be firmly connected to the bonded material (such as inorganic particles). The three-dimensional structure in the main chain polymer can greatly increase the sites of firm connection. The multi-dimensional hydrogen bond interactions in the main chain polymer make it easier to achieve the connection between the polymer and the bonded material (such as inorganic particles), thereby improving the bonding effect of the polymer.

[0092] When the binder in the separator includes the above polymer, the structure of the main chain polymer is a three-dimensional structure formed by intramolecular or intermolecular hydrogen bonds, such as Figure 1 As shown, the polymer is not prone to chain slip, the polymer has excellent mechanical strength, and the chelating agent in the binder is chelated and coordinated with the transition metal ions. The chelate formed by the chelation coordination has excellent stability, which can reversely increase the stability and mechanical strength of the binder and effectively protect the bonded materials (such as inorganic particles in the diaphragm) from falling off. In this way, the thermal stability of the diaphragm is higher, which makes the lithium battery have a lower safety risk during high-temperature cycling.

[0093] In some embodiments, the structural formula of the backbone polymer can be:

[0094]

[0095] Wherein, the repetition number of the structural unit shown in Formula I of the main chain polymer (i.e., the value range of n) is 15 to 300. For example, the repetition number of the structural unit shown in Formula I of the main chain polymer (i.e., the value range of n) can be 15, 50, 100, 150, 200, 250, and 300, or a value in the range formed by any two of the above points. When the repetition number of the structural unit shown in Formula I of the structural unit of the main chain polymer is controlled within the above range, the average molecular weight of the polymer is moderate, and the polymer has better bonding effect and mechanical properties.

[0096] In the embodiments of the present application, "polymer" refers to a polymer having side chains (such as the first side chain and / or the second side chain) attached to certain atoms of the main chain polymer. In the embodiments of the present application, the term "main chain polymer" may include a collection of macromolecules that are chemically uniform but different in degree of polymerization, molar mass and chain length prepared by polymerization, and may also include derivatives of such collections of macromolecules formed by polymerization, i.e., compounds that can be obtained by reaction of functional groups in the above macromolecules, such as addition or substitution, and may be chemically uniform or chemically inhomogeneous.

[0097] In some embodiments, the chelating agent comprises (ethylenediaminetetraacetic acid), (EDTA-3 sodium), (ethylenediaminetetraacetic acid 2-sodium base), (nitroethylethylenediaminetriacetate), (nitrilotriacetate), (ethylenediaminetetramethylene phosphate), (Diethylenetriaminepentaacetoxy), (ethylcarboxy-12-crown-4-ether), (Carboxyethyl-15-crown-5-ether) and (1-aza-8-carboxy-15-crown-5-ether)

[0098] In this way, the chelating agent may include multiple complexing sites (for example, the chelating agent may include multiple tertiary amino groups and multiple hydroxyl groups; for example, the chelating agent may include multiple tertiary amino groups and multiple hydroxyl substituents; for example, the chelating agent may include ether groups, carboxyl groups and / or secondary amino groups), and the multiple complexing sites may undergo multidentate coordination chelation with the transition metal ions in the electrolyte to form an inner orbital hybrid chelate, which has good stability and is not prone to dissociation, thereby reducing the probability of transition metal ions generated by chelate dissociation returning to the electrolyte; in this way, when the binder in the diaphragm includes the above-mentioned polymer, the diaphragm has an excellent effect of capturing transition metal ions, which can reduce the transfer of transition metal ions to the negative electrode of the lithium battery, the solid electrolyte interface film is not easily destroyed, the lithium battery has better cycle performance and storage performance, and can effectively prevent dendrites from piercing the diaphragm to cause internal short circuit of the battery, thereby reducing the probability of battery safety problems.

[0099] Furthermore, compared with the conventional scheme of amino-modified diaphragms, the amino-modified diaphragms will coordinate and complex with the transition metal ions in the electrolyte; the main chain polymer in the embodiment of the present application has abundant bonding sites of the first branch chain, and the polymer has abundant chelating agents, and each chelating agent can include multiple complexing sites, and the multiple complexing sites can be multi-dentately coordinated and chelated with the transition metal ions in the electrolyte to form an inner orbital hybrid chelate, so that the transition metal ions can be more easily captured through multi-dentate coordination and chelation, thereby improving the efficiency of capturing transition metal ions. In addition, the chelate has good stability, which can effectively alleviate the dissociation of the chelate, and the dissociated transition metal ions return to the electrolyte.

[0100] For example, the chelating agent is (ethylenediaminetetraacetic acid group), the chelating agent has three hydroxyl groups and two tertiary amino groups, and there are five complexing sites on the chelating agent. These five complexing sites can react with transition metal ions (such as Mn 2+ ) to carry out multidentate coordination chelation to form an intraorbital hybrid chelate.

[0101] For another example, the first branch is (diethylenetriaminepentaacetic acid group), the chelating agent has four hydroxyl groups and three tertiary amino groups, and there are seven complexing sites on the chelating agent, which can form a chelate with inner orbital hybridization by multidentate coordination with transition metal ions in the electrolyte. Here, only these two structures are used as examples for explanation, and the analysis process of the first branch of other structures is similar, which will not be repeated here.

[0102] In some embodiments, the structural unit of the backbone polymer may be:

[0103]

[0104] Wherein, the above Y1, Y2, and Y3 represent the bonding positions of the main chain polymer and a plurality of different first branches. In this way, different first branches can be introduced into the polymer according to actual needs, so that the polymer has a better transition metal ion (such as Mn 2+ ) capture capability.

[0105] In the embodiments of the present application, the above-mentioned Y1, Y2, and Y3 represent the bonding positions between the first main chain polymer and multiple different first branches, wherein the multiple different first branches include the following situations: the multiple first branches are all different, and some of the multiple first branches are the same.

[0106] For example, the chelating agent in the first branch bonded at the Y1 position can be (ethylenediaminetetraacetic acid group), the chelating agent in the first branch bonded at the Y2 position can be (nitrilotriacetate), the chelating agent in the first branch bonded at the Y3 position can be (ethylenediaminetetramethylene phosphate).

[0107] For example, the chelating agent in the first branch bonded at the Y1 position may be (nitroethylethylenediaminetriacetate), the chelating agent in the first branch bonded at the Y2 position can be (nitroethylethylenediaminetriacetate), the chelating agent in the first branch bonded at the Y3 position can be (ethylenediaminetetramethylene phosphate). These two examples are for illustration only, and other schemes may also be included, which can be explained with reference to the above two examples, and will not be repeated here.

[0108] In some embodiments, the structural formula of the backbone polymer can be:

[0109]

[0110] The repetition number of the above structural unit (ie the value range of m) is 5 to 100.

[0111] In some embodiments, the polymer includes a second branch chain, the second branch chain includes an active group, and the active group is used to increase the steric hindrance of the polymer. The main chain polymer includes a first main chain polymer, and the first main chain polymer includes a structural unit shown in Formula II.

[0112]

[0113] Wherein, R in Formula II represents the bonding position between the first main chain polymer and the second branch chain.

[0114] According to the above technical means, the second branch in the polymer includes an active group, which is used to increase the steric hindrance of the polymer, reduce the crystallinity of the polymer (increase the disorder of the polymer), and then improve the water solubility of the polymer, while the main chain polymer itself has an excellent bonding effect, so that a water-soluble polymer with excellent bonding effect can be obtained, and a water-soluble binder with excellent bonding effect can also be obtained. When the binder in the diaphragm includes the above polymer, the water-soluble binder with excellent bonding effect can better bond the bonded material (such as inorganic particles or base film in the diaphragm), which is conducive to improving the thermal stability of the diaphragm, so that the lithium battery has a lower safety risk during high-temperature cycling.

[0115] Furthermore, since the first main chain polymer has abundant functional group sites, the number of second branches on the polymer can be increased, which is beneficial to increase the number of active groups on the polymer, further improve the bonding effect of the binder, and help further improve the thermal stability of the diaphragm and improve the safety of lithium batteries during high-temperature cycles.

[0116] In some embodiments, the reactive group includes (carboxyl), (n=1-10) (sodium carboxyl), (n=1-10) (alkylcarboxyl), (n=1-10)(alkyl), (n=1-10) (alkanone group), (n=1-10) (alkene alkanoyl), (Lithium benzenesulfonate), At least one of .

[0117] In this way, the active groups of the above structure can increase the steric hindrance of the polymer, improve the disorder of the polymer, and then improve the water solubility of the polymer to obtain a water-soluble polymer with excellent bonding effect. When the binder in the diaphragm includes the above polymer, the water-soluble binder with excellent bonding effect can effectively protect the bonded material (such as inorganic particles in the diaphragm) from falling off. In this way, the thermal stability of the diaphragm is relatively high, so that the lithium battery has a lower safety risk during high-temperature cycling.

[0118] Preferably, the active groups include (Lithium benzenesulfonate), At least one of .

[0119] In this way, the second branch in the polymer includes an active group, and the active group can also include a functional group for transmitting lithium ions (anions and lithium ions bonded to the anions), which can significantly improve the lithium ion transmission effect of the polymer. The main chain polymer can also form a three-dimensional transmission channel, which can greatly improve the transmission rate of lithium ion transmission. When the binder in the diaphragm includes the above polymer, the binder has an excellent ion transmission effect, which is beneficial to improve the rate performance of the lithium battery. In addition, since the first main chain polymer has abundant functional group sites, the number of second branches on the polymer can be increased, which is beneficial to increase the number of active groups on the polymer, further improve the ion transmission effect of the binder, and improve the rate performance of the lithium battery.

[0120] Furthermore, the polymer has certain swelling properties. When the binder in the diaphragm includes the above polymer, the binder has the capacity to accommodate the electrolyte, which can further improve the ion transmission effect of the binder and improve the rate performance of the lithium battery.

[0121] For example, the active group is (lithium benzenesulfonate group), the active groups include oxygen ions and lithium ions bonded to the oxygen ions, so that the binder has excellent lithium ion transport effect.

[0122] For another example, the second branch is The active groups include two oxygen ions and lithium ions bonded to the two oxygen ions, so that the binder has an excellent lithium ion transport effect.

[0123] In some embodiments, the first backbone polymer may have a structural formula of:

[0124]

[0125] The number of repetitions of the structural unit represented by formula II of the first main chain polymer (ie, the value range of L) is 15 to 300.

[0126] In some embodiments, the polymer includes a plurality of different first branches, the main chain polymer includes a second main chain polymer, and the second main chain polymer includes a structural unit shown in Formula III,

[0127]

[0128] Wherein, Y1, Y2, and Y3 in Formula III represent the bonding positions between the second main chain polymer and a plurality of different first side chains.

[0129] In some embodiments, the polymer includes a plurality of different second branches, the main chain polymer includes a third main chain polymer, and the third main chain polymer includes a structural unit shown in Formula IV,

[0130]

[0131] Wherein, R1, R2, and R3 in Formula IV represent the bonding positions of the third main chain polymer and a plurality of different second side chains. In this way, different second side chains can be introduced into the polymer according to actual needs, so that the polymer has a better bonding effect.

[0132] In the embodiments of the present application, R1, R2, and R3 in Formula IV represent the bonding positions of the third main chain polymer and multiple different second branches, wherein the multiple different second branches include the following situations: the multiple second branches are all different, and some of the multiple second branches are the same.

[0133] For example, the active group in the second branch bonded at the R1 position in Formula IV can be (carboxyl), the active group in the second branch bonded at the R2 position in Formula IV can be (lithium benzenesulfonate group), the active group in the second branch bonded at the R3 position in Formula IV can be

[0134] For example, the active group in the second branch bonded at the R1 position in Formula IV can be (carboxyl), the active group in the second branch bonded at the R2 position in Formula IV can be The active group in the second branch bonded at the R3 position in Formula IV can be These two examples are for illustration only. Other solutions may also be included. You can refer to the above two examples for illustration, and will not go into details here.

[0135] In some embodiments, the structural formula of the backbone polymer can be:

[0136]

[0137] The number of repetitions of the structural unit represented by formula IV of the main chain polymer (ie, the value range of P) is 5 to 100.

[0138] In some embodiments, the polymer further comprises a polar group (such as the hydroxyl group of the following formula), which is bonded to the main chain polymer. The polar group can further increase the bonding effect of the polymer;

[0139]

[0140] In some embodiments, the weight average molecular weight of the polymer is 400,000 to 1,000,000. For example, the weight average molecular weight of the polymer can be 400,000, 500,000, 600,000, 700,000, 800,000, 900,000, 1,000,000, or a value in the range of any two of the above points.

[0141] By controlling the weight average molecular weight of the above polymer within the above range, the average molecular weight of the polymer is moderate, and the polymer has better bonding effect and mechanical properties. In addition, it can alleviate the situation that the weight average molecular weight of the polymer is too low, resulting in low mechanical strength of the polymer, and the corresponding diaphragm is prone to deformation, and it can also alleviate the situation that the weight average molecular weight of the polymer is too high, resulting in poor bonding effect of the polymer.

[0142] The embodiment of the present application provides a method for preparing the polymer of the above embodiment, comprising: subjecting a first polymer, an amidation agent, and a chelating agent to an amidation reaction in an aqueous solvent to obtain a polymer;

[0143] Wherein, the first polymer includes a structural unit as shown in the following formula V,

[0144]

[0145] In an aqueous solvent, the first polymer, the amidation agent, and the chelating agent are subjected to an amidation reaction, and the chelating agent can be introduced into the amino group on the first polymer to obtain a structural unit polymer having Formula I. The amount of the chelating agent can be selectively added according to actual needs, and the embodiment of the present application is not limited thereto.

[0146] In some embodiments, the amidation reaction includes: dispersing the first polymer into an aqueous solvent to obtain a first mixture, adding an alkaline substance (such as sodium hydroxide) to the first mixture to make it alkaline; then adding an amidating agent (such as carbodiimide) and a chelating agent (such as ethylenediaminetetraacetic acid) to the first mixture, stirring to obtain a second mixture; finally, adding an acidic substance to the second mixture until the second mixture is neutral, and precipitating to obtain a polymer. For example, the polymer obtained by precipitation can be purified to obtain a high-purity polymer, wherein the purification can include filtering, washing, and drying.

[0147] In some possible embodiments, the first polymer includes chitosan. In some possible embodiments, the amidation agent includes carbodiimide. In some possible embodiments, the aqueous solvent includes deionized water and pure water. Of course, the first polymer, the amidation agent, and the aqueous solvent can be selected from other substances according to actual conditions, and the embodiments of the present application are not limited here.

[0148] In some possible embodiments, the mass ratio of the first polymer to the amidation agent is 1:(1-10), for example, the mass ratio of the first polymer to the amidation agent can be 1:1, 1:3, 1:5, 1:7, 1:9, 1:10. In this way, the effect of the amidation reaction is better, and the yield of the prepared polymer can be improved. In some possible embodiments, the reaction temperature of the amidation reaction can be 50°C-70°C, for example, 50°C, 55°C, 60°C, 65°C, 70°C.

[0149] In some embodiments, the method for preparing a polymer may further include: subjecting a first polymer and a carboxylating agent to a carboxylating reaction to obtain a carboxylated first polymer; and subjecting the carboxylated first polymer, an amidating agent, and a chelating agent to an amidation reaction under acidic conditions to an alkylation reaction. In this scheme, an active group including a carboxyl group may be first introduced into the first polymer through a carboxylating reaction, and then a chelating agent may be introduced into the first polymer through an amidation reaction, which may greatly improve the water solubility of the prepared polymer, thereby facilitating the improvement of the water-soluble bonding effect of the binder, and may greatly improve the manganese ion capture effect of the binder after the amidation reaction.

[0150] In some embodiments, the carboxylation reaction includes: dispersing the first polymer into an acidic substance (such as hydrochloric acid) to obtain a third mixture, adding an alkaline substance (such as sodium hydroxide) to the third mixture to make it alkaline; then adding a carboxylation agent (such as chloroacetic acid) to the third mixture, after reflux reaction, adding an acidic substance to the third mixture to make it neutral, and precipitating to obtain the carboxylated first polymer. For example, the precipitated carboxylated first polymer can be purified to obtain a high-purity polymer, wherein the purification can include steps such as filtering, washing, and drying.

[0151] In some possible embodiments, the mass ratio of the first polymer to the carboxylation agent is 1:(1-5), for example, the mass ratio of the first polymer to the carboxylation agent can be 1:1, 1:2, 1:3, 1:4, 1:5. In this way, the effect of the carboxylation reaction is better. In some possible embodiments, the reaction temperature of the carboxylation reaction can be 50°C-70°C, for example, 50°C, 55°C, 60°C, 65°C, 70°C.

[0152] In some possible embodiments, the carboxylating agent may be The carboxylating agent corresponding to the groups such as chloroacetic acid can be used.

[0153] In some embodiments, the method for preparing a polymer may further include: subjecting a first polymer and an alkylating agent to an alkylation reaction to obtain an alkylated first polymer; and subjecting the alkylated first polymer, an amidating agent, and a chelating agent to an amidation reaction under acidic conditions to perform an alkylation reaction. In this scheme, an active group including an alkyl group may be first introduced into the first polymer through an alkylation reaction, and then a chelating agent may be introduced into the first polymer through an amidation reaction, which may greatly improve the water solubility of the prepared polymer, thereby facilitating the improvement of the water-soluble bonding effect of the binder, and may greatly improve the manganese ion capture effect of the binder after the amidation reaction.

[0154] In some embodiments, the alkylation reaction includes: dispersing the first polymer into an acidic substance (such as hydrochloric acid) to obtain a fourth mixture, adding an alkaline substance (such as sodium hydroxide) to the fourth mixture to make it alkaline; then adding an activator (such as an alkylating anhydride) to the third mixture, after reflux reaction, adding an acidic substance to the fourth mixture to make it neutral, and precipitating to obtain the alkylated first polymer. For example, the precipitated alkylated first polymer can be purified to obtain a high-purity polymer, wherein the purification can include steps such as filtering, washing and drying.

[0155] It should be noted that the first mixture to the fourth mixture are only for convenience of reference and limit the preparation order.

[0156] In some possible embodiments, the mass ratio of the first polymer to the alkylating agent is 1:(1-5), for example, the mass ratio of the first polymer to the alkylating agent can be 1:1, 1:2, 1:3, 1:4, 1:5. In this way, the effect of the alkylation reaction is better. In some possible embodiments, the reaction temperature of the alkylation reaction can be 50°C-70°C, for example, 50°C, 55°C, 60°C, 65°C, 70°C.

[0157] In some possible embodiments, the alkylating agent may be The alkylating agent corresponding to the group may be, for example, an alkylating anhydride.

[0158] The embodiments of the present application provide a binder, and the binder includes the polymer of the above embodiment. In this way, the binder has excellent ability to capture transition metal ions, lithium ion transmission ability, water-soluble bonding effect and mechanical properties. In addition, compared with organic solvents, the binder provided in the embodiments of the present application avoids the use of toxic organic solvents, and is rich in sources, and can replace the binder in the existing lithium battery system for use, and the binder provided in the embodiments of the present application can be compatible with the diaphragm preparation process for industrial application, can be applied on a large scale, and is simple to operate, easy to control, and has a large application prospect, which is conducive to solving the problem that it is difficult to introduce a single complexing agent into the lithium battery system, the complexing efficiency is low, and it is easy to affect the performance of the lithium battery.

[0159] The embodiment of the present application provides a diaphragm, referring to Figure 3 The diaphragm includes a substrate layer and at least one coating layer disposed on the surface of the substrate layer, the substrate layer includes a base film, and the coating layer includes the binder and inorganic particles of the above embodiment. In some possible implementations, the diaphragm includes a base film and a film layer disposed on at least one surface of the base film, the film layer includes inorganic particles, and the binder of the above embodiment.

[0160] In this way, firstly, the above-mentioned diaphragm can effectively capture the transition metal ions in the electrolyte, and effectively prevent the transition metal ions in the positive electrode material from being transferred to the negative electrode through the electrolyte; secondly, the binder in the above-mentioned diaphragm has an excellent water-soluble bonding effect. Figure 4 , which can achieve good bonding between the base film and the inorganic particles; thirdly, the above-mentioned diaphragm has excellent lithium ion transmission capability; fourthly, the above-mentioned diaphragm has good mechanical properties, which can reduce the probability of inorganic particles on the diaphragm falling off and improve the thermal stability of the diaphragm in a high-temperature cycle environment.

[0161] In some embodiments, the mass fraction of the binder in the separator is 0.01% to 10%. For example, the mass fraction of the binder in the separator is 0.01%, 1%, 3%, 5%, 7%, 10%. Controlling the mass fraction of the binder in the separator within the above range is conducive to achieving good bonding between the base film and the inorganic particles.

[0162] In some embodiments, the base film comprises at least one of a polyethylene (PE) film, a polypropylene (PP) film, a PP / PE double-layer film, a PP / PE / PP three-layer film, a polyvinylidene fluoride (PVDF) film, a polyimide (PI) film, and a polymer nanofiber film. In some possible embodiments, the thickness of the polymer porous film is 4 microns to 40 microns; for example, the thickness of the base film can be 4 microns, 10 microns, 15 microns, 20 microns, 25 microns, 30 microns, 35 microns and 40 microns, or a value in the range of any two of the above points. In some possible embodiments, the pore size of the base film is 10 nanometers to 2000 nanometers, for example, the pore size of the base film can be 10 nanometers, 50 nanometers, 100 nanometers, 500 nanometers, 1500 nanometers and 2000 nanometers, or a value in the range of any two of the above points.

[0163] In some embodiments, the inorganic particles include aluminum oxide (Al2O3), aluminum oxyhydroxide (AlOOH), silicon dioxide (SiO2), titanium dioxide (TiO2), boron nitride (BN), zirconium dioxide (ZrO2), Li 1.5 Al 0.5 Ti 1.5 (PO4)3(LATP), Li 0.5 La 0.5 TiO3 (LLTO) and one or more mixtures thereof. In some possible embodiments, the particle size of the inorganic particles is 30 nanometers to 10,000 nanometers. For example, the particle size of the inorganic particles can be 30 nanometers, 100 nanometers, 500 nanometers, 1,000 nanometers, 5,000 nanometers and 10,000 nanometers, or a value in the range of any two of the above points. In this way, the use of the above-mentioned high-temperature resistant inorganic particles can significantly improve the high-temperature resistance of the diaphragm.

[0164] In some embodiments, the porosity of the diaphragm is 40% to 60%. For example, the porosity of the bifunctional diaphragm can be 40%, 43%, 46%, 49%, 51%, 54%, 57%, 60%, or a value in the range of any two of the above points. Controlling the porosity of the diaphragm within the above range can alleviate the problems of excessive porosity, resulting in low strength of the diaphragm and insufficient electrolyte retention capacity, and can also alleviate the problem of too small porosity of the diaphragm, which affects the pores of lithium ions passing through the diaphragm.

[0165] In some embodiments, the thickness of the diaphragm is 5 microns to 45 microns. For example, the thickness of the diaphragm can be 5 microns, 10 microns, 15 microns, 20 microns, 25 microns, 30 microns, 35 microns, 40 microns and 45 microns, or a value in the range of any two of the above points. Controlling the thickness of the diaphragm within the above range can alleviate the diaphragm being too thick, increasing the internal resistance of the lithium battery, and reducing the electrochemical performance of the lithium battery, and can also alleviate the diaphragm being too thin, the mechanical strength of the diaphragm is poor, it is easy to rupture, and the safety risk of the battery is greater.

[0166] In some embodiments, the coating layer in the membrane has a thickness of 1 μm to 5 μm. For example, the coating layer in the membrane has a thickness of 1 μm, 2 μm, 3 μm, 4 μm and 5 μm, or a value in a range formed by any two of the above points.

[0167] The embodiment of the present application provides a method for preparing a diaphragm. The method for preparing a binder may include the following steps:

[0168] S100: preparing a diaphragm slurry.

[0169] In some embodiments, deionized water, inorganic particles and a binder including the above polymer are mixed to obtain a diaphragm slurry. In some possible implementations, deionized water and a dispersant are first mixed, and then inorganic particles are added for stirring and dispersion to uniformly mix the inorganic particles and the dispersant, and finally a binder is added for stirring and dispersion to obtain a diaphragm slurry.

[0170] In some possible embodiments, the dispersant comprises at least one of ammonium polyacrylate, sodium polyacrylate, potassium polyacrylate, organic alcohols, BYK-ET-3030, and BYK-ET-3032. In some possible embodiments, the dispersing method of adding inorganic particles for stirring and dispersing comprises at least one of mechanical stirring, double planetary stirring, ultrasonic dispersion, and sand mill dispersion, wherein the stirring speed may be 200 rpm / min to 5000 rpm / min, and the stirring time may be 10 min to 120 min. In some possible embodiments, the dispersing method of adding a binder for stirring and dispersing comprises at least one of mechanical stirring, double planetary stirring, ultrasonic dispersion, and sand mill dispersion, wherein the stirring speed may be 200 rpm / min to 5000 rpm / min, and the stirring time may be 10 min to 120 min.

[0171] In some embodiments, the diaphragm slurry comprises inorganic particles, deionized water, a dispersant and a binder, wherein the weight ratio of the inorganic particles, deionized water, the dispersant and the binder is (30-40): (50-60): (0.1-2): (1-12).

[0172] The weight ratio of inorganic particles, deionized water, dispersant and binder is controlled within the above range. The inorganic particles, deionized water, dispersant and binder are all moderate. The inorganic particles and binder can be evenly distributed in the plasma water, which is beneficial to improve the uniformity of the diaphragm, and the lithium battery has better battery performance.

[0173] In some embodiments, the viscosity of the diaphragm slurry is 500mPa.s to 3000mPa.s. For example, the viscosity of the diaphragm slurry can be 500mPa.s, 1000mPa.s, 1500mPa.s, 2000mPa.s, 2500mPa.s and 3000mPa.s, or a value in the range formed by any two of the above points. Controlling the viscosity of the diaphragm slurry within the above range can alleviate the high viscosity of the diaphragm slurry, which makes coating more difficult and easily causes inconsistency in the battery performance of the lithium battery. It can also alleviate the low viscosity of the diaphragm slurry, which may cause the quality of the diaphragm to decline and easily cause the safety of the lithium battery to decline.

[0174] S200: Applying the diaphragm slurry on at least one side of the base film to obtain a diaphragm.

[0175] In some embodiments, the diaphragm slurry is coated on at least one side of the diaphragm, and the diaphragm slurry is dried to obtain the diaphragm.

[0176] In some embodiments, the membrane slurry is coated on at least one side of the membrane by a coating method such as micro-dimple coating, spot coating, spray coating, dip coating, or scraper coating.

[0177] In some embodiments, the drying conditions are as follows: the drying temperature is 50°C to 100°C, and the drying time is 5min to 120min. For example, the drying temperature may be 50°C, 60°C, 70°C, 80°C, 90°C, and 100°C, and the drying time may be 5min, 10min, 30min, 50min, 80min, 100min, and 120min, or a value in the range of any two of the above points. By controlling the drying temperature and the drying time within the above range, rapid drying of the diaphragm slurry can be achieved.

[0178] An embodiment of the present application provides a manganese-based lithium battery, which includes a separator having a polymer.

[0179] In this way, first, if the manganese-based positive electrode material of the manganese-based lithium battery undergoes Mn 2+Dissolution phenomenon, the polymer diaphragm can effectively capture the transition metal ions in the electrolyte, effectively avoid the transition metal ions in the positive electrode material from being transferred to the negative electrode through the electrolyte, improve the rate performance and cycle life of the manganese-based lithium battery, and improve the safety of the manganese-based lithium battery; second, the base film and inorganic particles in the above-mentioned diaphragm have good adhesion, and the inorganic particles are not prone to fall off, which can improve the thermal stability of the manganese-based lithium battery; third, the above-mentioned diaphragm has excellent lithium ion transmission ability, which improves the rate performance and cycle life of the manganese-based lithium battery; fourth, the above-mentioned diaphragm has good mechanical properties, which can reduce the probability of inorganic particles on the diaphragm falling off, and improve the thermal stability of the manganese-based lithium battery in a high-temperature cycle environment.

[0180] In some embodiments, the manganese-based positive electrode material of the manganese-based lithium battery includes lithium iron manganese phosphate (LiMn 1-x Fe x PO4), lithium manganese oxide LiMn2O4, lithium manganese phosphate LiMnPO4, lithium nickel manganese oxide LiNi 0.5 Mn 1.5 O4, lithium-rich manganese-based (xLi2MnO3(1-x)LiMO2, M═Ni, Co, Mn, etc.) at least one.

[0181] In some embodiments, the negative electrode material of the manganese-based lithium-ion battery includes at least one of silicon / carbon, graphite, lithium titanate and metallic lithium. In some embodiments, the electrolyte system in the manganese-based lithium battery includes at least one of a carbonate electrolyte and a gel electrolyte. In some embodiments, the electrolyte system in the manganese-based lithium battery includes a solvent and a lithium salt, wherein the solvent includes at least one of carbonate and organic ether solvents such as ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene glycol dimethyl ether (DMC);

[0182] The lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium chloride, lithium tris(pentafluoroethyl)trifluorophosphate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorobis(oxalatophosphate), lithium tetrafluorooxalatophosphate and lithium carbonate.

[0183] The embodiment of the present application provides a method for preparing a manganese-based lithium battery, and the method for preparing a manganese-based lithium battery includes: preparing a positive electrode sheet using a manganese-based positive electrode material as a positive electrode active material, preparing a negative electrode sheet using graphite as a negative electrode active material, and using the above-mentioned diaphragm with a polymer as a battery diaphragm; placing the positive electrode sheet and the negative electrode sheet on both sides of the battery diaphragm, respectively, winding or stacking them into a sandwich structure to form a dry battery cell, putting them into a bag / shell, injecting an electrolyte, and packaging to obtain a manganese-based lithium battery.

[0184] The embodiment of the present application provides a vehicle, which includes the manganese-based lithium battery of the above embodiment. In this way, the vehicle has a longer service life and higher safety.

[0185] The following describes the embodiments of the present application. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.

[0186] In the following examples and comparative examples, the first branch chain (ie, Y1 / Y2 / Y3) can be generated by an amidation reaction, and the second branch chain (ie, R1 / R2 / R3) can be generated by a carboxylation reaction or an alkylation reaction. The structural formula of the polymer is:

[0187] The polymers prepared by the above method are defined, and the polymers of Examples 1-30 and Comparative Examples 1-5 are named R1 / R2 / R3-CSn-Y1 / Y2 / Y3, wherein CS in CSn represents the repeating structural unit of the main chain polymer, and n represents the number of structural units of the main chain polymer. Referring to Table 3, Y10-Y19 represents the possible structures of Y1; Y20-Y29 represents the possible structures of Y2; Y30-Y39 represents the possible structures of Y3; referring to Table 4, R10-R19 represents the possible structures of R1; R20-R29 represents the possible structures of R2; and R30-R39 represents the possible structures of R3. The polymers prepared in Examples 1-30 are binders.

[0188] Example 1

[0189] (1) Type of binder.

[0190] The adhesive is CS25-Y10 / Y20 / Y30.

[0191] (2) Preparation of a diaphragm.

[0192] (2-1) Preparation of diaphragm slurry:

[0193] After deionized water and sodium polyacrylate (dispersant) are mixed, a sand mill is used to stir and disperse them at a stirring rate of 600 rpm / min for 20 min; Al2O3 inorganic ceramic particles (inorganic particles) with a particle size of 450 nanometers are then added, and a sand mill is used to stir and disperse them at a stirring rate of 2000 rpm / min for 30 min; finally, the binder prepared in step (1) is added, and a sand mill is used to stir and disperse them at a stirring rate of 1000 rpm / min for 60 min to obtain a diaphragm slurry; wherein the viscosity of the diaphragm slurry is 1500 mPa.s;

[0194] (2-2) Preparation of a diaphragm.

[0195] A polypropylene porous membrane with a thickness of 40 μm and a pore size of 50 nm was selected as the base membrane; the polypropylene porous membrane was placed on a micro-dimpled coating machine, and the diaphragm slurry obtained in step (2-1) was evenly coated on both sides of the polypropylene porous membrane, and placed in an oven at 80° C. for 60 min to obtain a diaphragm with a total thickness of 44 μm, wherein the membrane layer formed by the diaphragm slurry was 2 μm, and in the membrane layer formed by the diaphragm slurry, the weight ratio of inorganic particles to dispersant was 30:0.5;

[0196] (3) Preparation of manganese-based lithium batteries.

[0197] LiMn2O4 is selected as the positive electrode active material to prepare a positive electrode sheet, which is cut by a cutting machine to obtain a positive electrode sheet with a width of 5 cm and a length of 7 cm; graphite is selected as the negative electrode active material to prepare a negative electrode sheet, which is cut by a cutting machine to obtain a negative electrode sheet with a width of 7 cm and a length of 9 cm; the diaphragm prepared in step (2-2) is cut by a cutting machine to obtain a diaphragm with a width of 12 cm and a length of 90 cm; the cut positive electrode sheet, diaphragm and negative electrode sheet are stacked and assembled into a manganese-based lithium battery dry cell, which is then put into a shell, an organic electrolyte is injected, and the cell is sealed to obtain a manganese-based lithium-ion battery, which is then formed, divided and tested for comprehensive electrochemical performance according to conventional industrial processes.

[0198] Example 2

[0199] The difference between Example 2 and Example 1 is:

[0200] (1) The adhesive is R10 / R20 / R30-CS25-Y10 / Y20 / Y30.

[0201] Example 3

[0202] (1) Type of binder.

[0203] The adhesive is R10 / R20 / R30-CS25-Y10 / Y20 / Y3.

[0204] (2) Preparation of a diaphragm.

[0205] (2-1) Preparation of diaphragm slurry:

[0206] After deionized water and sodium polyacrylate (dispersant) are mixed, a sand mill is used to stir and disperse them at a stirring rate of 600 rpm / min for 20 min; SiO2 inorganic ceramic particles (inorganic particles) with a particle size of 450 nanometers are then added, and a sand mill is used to stir and disperse them at a stirring rate of 5000 rpm / min for 60 min; finally, the binder prepared in step (1) is added, and a sand mill is used to stir and disperse them at a stirring rate of 1000 rpm / min for 60 min to obtain a diaphragm slurry; wherein the viscosity of the diaphragm slurry is 500 mPa.s;

[0207] (2-2) Preparation of diaphragm

[0208] A polypropylene porous membrane with a thickness of 4 microns and a pore size of 10 nanometers is selected as the base membrane; the polypropylene porous membrane is placed on a micro-dimpled coating machine, and the diaphragm slurry obtained in step (2-1) is evenly coated on both sides of the polypropylene porous membrane, and placed in an oven at 100°C for 120 minutes to obtain a diaphragm with a total thickness of 14 microns, wherein the membrane layer formed by the diaphragm slurry is 5 microns, and in the membrane layer formed by the diaphragm slurry, the weight ratio of inorganic particles to dispersant is 35:2;

[0209] (3) Preparation of manganese-based lithium batteries.

[0210] LiMn2O4 is selected as the positive electrode active material to prepare a positive electrode sheet, which is cut by a cutting machine to obtain a positive electrode sheet with a width of 5 cm and a length of 7 cm; graphite is selected as the negative electrode active material to prepare a negative electrode sheet, which is cut by a cutting machine to obtain a negative electrode sheet with a width of 7 cm and a length of 9 cm; the diaphragm prepared in step (2-2) is cut by a cutting machine to obtain a diaphragm with a width of 12 cm and a length of 90 cm; the cut positive electrode sheet, diaphragm and negative electrode sheet are stacked and assembled into a manganese-based lithium battery dry cell, which is then put into a shell, an organic electrolyte is injected, and the cell is sealed to obtain a manganese-based lithium-ion battery, which is then formed, divided and tested for comprehensive electrochemical performance according to conventional industrial processes.

[0211] Example 4

[0212] (1) Type of binder.

[0213] The adhesive is R10 / R20 / R30-CS25-Y10 / Y20 / Y30.

[0214] (2) Preparation of a diaphragm.

[0215] (2-1) Preparation of diaphragm slurry:

[0216] After deionized water and sodium polyacrylate (dispersant) are mixed, a sand mill is used to stir and disperse them at a stirring rate of 1000 rpm / min for 10 min; AlOOH inorganic ceramic particles (inorganic particles) with a particle size of 850 nanometers are then added, and a sand mill is used to stir and disperse them at a stirring rate of 3000 rpm / min for 60 min; finally, the binder prepared in step (1) is added, and a sand mill is used to stir and disperse them at a stirring rate of 1000 rpm / min for 60 min to obtain a diaphragm slurry; wherein the viscosity of the diaphragm slurry is 3000 mPa.s;

[0217] (2-2) Preparation of diaphragm

[0218] A polypropylene (PP) / polyethylene (PE) porous membrane with a thickness of 20 microns and a pore size of 10 nanometers is selected as the base membrane; the polypropylene (PP) / polyethylene (PE) porous membrane is placed on a point coating coating machine, and the diaphragm slurry obtained in step (2-1) is evenly coated on both sides of the polypropylene (PP) / polyethylene (PE) porous membrane, and placed in a 50°C oven for drying for 120 minutes to obtain a diaphragm with a total thickness of 22 microns, wherein the membrane layer formed by the diaphragm slurry is 1 micron, and in the membrane layer formed by the diaphragm slurry, the weight ratio of inorganic particles to dispersant is 40:0.1;

[0219] (3) Preparation of manganese-based lithium batteries.

[0220] LiMn2O4 is selected as the positive electrode active material to prepare a positive electrode sheet, which is cut by a cutting machine to obtain a positive electrode sheet with a width of 5 cm and a length of 7 cm; graphite is selected as the negative electrode active material to prepare a negative electrode sheet, which is cut by a cutting machine to obtain a negative electrode sheet with a width of 7 cm and a length of 9 cm; the diaphragm prepared in step (2-2) is cut by a cutting machine to obtain a diaphragm with a width of 12 cm and a length of 90 cm; the cut positive electrode sheet, diaphragm and negative electrode sheet are stacked and assembled into a manganese-based lithium battery dry cell, which is then put into a shell, an organic electrolyte is injected, and the cell is sealed to obtain a manganese-based lithium-ion battery, which is then formed, divided and tested for comprehensive electrochemical performance according to conventional industrial processes.

[0221] Example 5

[0222] The difference between Example 5 and Example 2 is that:

[0223] (1) The adhesive is R10 / R20 / R30-CS5-Y10 / Y20 / Y30.

[0224] Example 6

[0225] The difference between Example 6 and Example 2 is:

[0226] (1) The adhesive is R10 / R20 / R30-CS100-Y10 / Y20 / Y30.

[0227] Example 7

[0228] The difference between Example 7 and Example 2 is:

[0229] (1) Types of binders

[0230] The adhesive is R10 / R20 / R30-CS70-Y10 / Y20 / Y30.

[0231] Example 8

[0232] (1) Type of binder.

[0233] The adhesive is R10 / R21 / R35-CS25-Y10 / Y20 / Y30.

[0234] (2) Preparation of a diaphragm.

[0235] (2-1) Preparation of diaphragm slurry:

[0236] After deionized water and sodium polyacrylate (dispersant) are mixed, a double planetary mixer is used for stirring and dispersing at a stirring rate of 1500 rpm / min and a stirring time of 20 min; then LATP inorganic ceramic particles (inorganic particles) with a particle size of 600 nanometers are added, and a sand mill is used for stirring and dispersing at a stirring rate of 2000 rpm / min and a stirring time of 30 min; finally, the binder prepared in step (1) is added, and a sand mill is used for stirring and dispersing at a stirring rate of 1000 rpm / min and a stirring time of 60 min to obtain a diaphragm slurry; wherein the viscosity of the diaphragm slurry is 3000 mPa.s;

[0237] (2-2) Preparation of diaphragm

[0238] A polypropylene (PP) / polyethylene (PE) / polypropylene (PP) porous membrane with a thickness of 16 microns and a pore size of 50 nanometers is selected as the base membrane; the polypropylene (PP) / polyethylene (PE) porous membrane is placed on a micro-dimpled coating machine, and the diaphragm slurry obtained in step (2-1) is evenly coated on both sides of the polypropylene (PP) / polyethylene (PE) porous membrane, and placed in an oven at 80°C for 100 minutes to obtain a diaphragm with a total thickness of 20 microns, wherein the membrane layer formed by the diaphragm slurry is 2 microns, and in the membrane layer formed by the diaphragm slurry, the weight ratio of inorganic particles to dispersant is 30:0.5;

[0239] (3) Preparation of manganese-based lithium batteries.

[0240] LiMn6Fe4PO4 is selected as the positive electrode active material to prepare a positive electrode sheet, which is cut by a cutting machine to obtain a positive electrode sheet with a width of 5 cm and a length of 7 cm; graphite is selected as the negative electrode active material to prepare a negative electrode sheet, which is cut by a cutting machine to obtain a negative electrode sheet with a width of 7 cm and a length of 9 cm; the diaphragm prepared in step (2-2) is cut by a cutting machine to obtain a diaphragm with a width of 12 cm and a length of 90 cm; the cut positive electrode sheet, diaphragm and negative electrode sheet are stacked and assembled into a manganese-based lithium battery dry cell, which is then put into a shell, an organic electrolyte is injected, and the cell is sealed to obtain a manganese-based lithium-ion battery, which is then formed, divided and tested for comprehensive electrochemical performance according to conventional industrial processes.

[0241] Example 9

[0242] (1) Type of binder.

[0243] The adhesive is R10 / R23 / R36-CS25-Y10 / Y20 / Y30.

[0244] (2) Preparation of a diaphragm.

[0245] (2-1) Preparation of diaphragm slurry:

[0246] After deionized water and sodium polyacrylate (dispersant) are mixed, a sand mill is used to stir and disperse them at a stirring rate of 600 rpm / min for 20 min; SiO2 inorganic ceramic particles (inorganic particles) with a particle size of 30 nanometers are then added, and a sand mill is used to stir and disperse them at a stirring rate of 5000 rpm / min for 60 min; finally, the binder prepared in step (1) is added, and a sand mill is used to stir and disperse them at a stirring rate of 1000 rpm / min for 60 min to obtain a diaphragm slurry; wherein the viscosity of the diaphragm slurry is 1000 mPa.s;

[0247] (2-2) Preparation of diaphragm

[0248] A polyethylene (PE) porous membrane with a thickness of 12 microns and a pore size of 10 nanometers is selected as the base membrane; the above-mentioned polypropylene (PP) / polyethylene (PE) porous membrane is placed on a sprayer, and the diaphragm slurry obtained in step (2-1) is evenly coated on both sides of the polyethylene (PE) porous membrane, and placed in an oven at 100°C for 120 minutes to obtain a diaphragm with a total thickness of 22 microns, wherein the membrane layer formed by the diaphragm slurry is 5 microns, and in the membrane layer formed by the diaphragm slurry, the weight ratio of inorganic particles to dispersant is 35:2;

[0249] (3) Preparation of manganese-based lithium batteries.

[0250] Select xLi2MnO3(1-x)LiMO2 as the positive electrode active material to prepare the positive electrode sheet, and cut it by a cutting machine to obtain a positive electrode sheet with a width of 5 cm and a length of 7 cm; select graphite as the negative electrode active material to prepare the negative electrode sheet, and cut it by a cutting machine to obtain a negative electrode sheet with a width of 7 cm and a length of 9 cm; cut the diaphragm prepared in step (2-2) by a cutting machine to obtain a diaphragm with a width of 12 cm and a length of 90 cm; stack the cut positive electrode sheet, diaphragm and negative electrode sheet to assemble into a manganese-based lithium battery dry cell, then put it into a shell, inject an organic electrolyte, and seal it to obtain a manganese-based lithium-ion battery. Subsequently, it is formed, divided and tested for comprehensive electrochemical properties according to conventional industrial processes.

[0251] Example 10

[0252] (1) Type of binder.

[0253] The adhesive is R12 / R28 / R36-CS25-Y10 / Y20 / Y30.

[0254] (2) Preparation of a diaphragm.

[0255] (2-1) Preparation of diaphragm slurry:

[0256] After deionized water and ethylene glycol (dispersant) are mixed, magnetic stirring is performed at a rate of 500 rpm / min for 15 min; TiO2 inorganic ceramic particles (inorganic particles) with a particle size of 30 nanometers are then added, magnetic stirring is performed at a rate of 2000 rpm / min for 60 min; finally, the binder prepared in step (1) is added, magnetic stirring is performed at a rate of 2000 rpm / min for 60 min to obtain a diaphragm slurry; wherein the viscosity of the diaphragm slurry is 2000 mPa.s;

[0257] (2-2) Preparation of diaphragm

[0258] A PVDF nanofiber porous membrane with a thickness of 40 microns and a pore size of 2 nanometers is selected as the base membrane; the above-mentioned PVDF nanofiber porous membrane is placed on a point coating coating machine, and the diaphragm slurry obtained in step (2-1) is evenly coated on both sides of the polyethylene (PE) porous membrane, and placed in a 50°C oven for drying for 120 minutes to obtain a diaphragm with a total thickness of 42 microns, wherein the membrane layer formed by the diaphragm slurry is 1 micron, and in the membrane layer formed by the diaphragm slurry, the weight ratio of inorganic particles to dispersant is 40:0.1;

[0259] (3) Preparation of manganese-based lithium batteries.

[0260] Select LiNi 0.5 Mn 1.5O4 is used as the positive electrode active material to prepare a positive electrode sheet, which is cut by a cutting machine to obtain a positive electrode sheet with a width of 5 cm and a length of 7 cm; graphite is selected as the negative electrode active material to prepare a negative electrode sheet, which is cut by a cutting machine to obtain a negative electrode sheet with a width of 7 cm and a length of 9 cm; the diaphragm prepared in step (2-2) is cut by a cutting machine to obtain a diaphragm with a width of 12 cm and a length of 90 cm; the cut positive electrode sheet, diaphragm and negative electrode sheet are stacked and assembled into a manganese-based lithium battery dry cell, which is then put into a shell, an organic electrolyte is injected, and the cell is sealed to obtain a manganese-based lithium-ion battery, which is then formed, divided and tested for comprehensive electrochemical properties according to conventional industrial processes.

[0261] Embodiment 11

[0262] The difference between Example 11 and Example 2 is:

[0263] The adhesive is R12 / R28 / R36-CS25-Y10 / Y20 / Y30.

[0264] Example 12

[0265] The difference between Example 12 and Example 2 is that:

[0266] (1) The adhesive is R10 / R23 / R36-CS25-Y10 / Y20 / Y30.

[0267] Embodiment 13

[0268] The difference between Example 13 and Example 2 is that:

[0269] (1) The adhesive is R10 / R21 / R35-CS25-Y10 / Y20 / Y30.

[0270] Embodiment 14

[0271] The difference between Example 14 and Example 2 is that:

[0272] (1) The adhesive is R16 / R26 / R39-CS25-Y10 / Y20 / Y30.

[0273] Embodiment 15

[0274] (1) Type of binder.

[0275] The adhesive is R10 / R20 / R30-CS50-Y11 / Y23 / Y35.

[0276] (2) Preparation of a diaphragm.

[0277] (2-1) Preparation of diaphragm slurry:

[0278] After deionized water and potassium polyacrylate (dispersant) are mixed, a double planetary mixer is used at a stirring rate of 1500 rpm / min for 20 min; then LATP inorganic ceramic particles (inorganic particles) with a particle size of 600 nanometers are added, and magnetic stirring is used at a stirring rate of 2000 rpm / min for 30 min; finally, the binder prepared in step (1) is added, and magnetic stirring is used at a stirring rate of 1000 rpm / min for 60 min to obtain a diaphragm slurry; wherein the viscosity of the diaphragm slurry is 3000 mPa.s;

[0279] (2-2) Preparation of diaphragm

[0280] A PI porous membrane with a thickness of 20 μm and a pore size of 100 nm was selected as the base membrane; the above-mentioned PVDF nanofiber porous membrane was placed on a micro-dimpled coating machine, and the diaphragm slurry obtained in step (2-1) was evenly coated on both sides of the PI porous membrane, and placed in an oven at 80°C for 100 min to obtain a diaphragm with a total thickness of 24 μm, wherein the membrane layer formed by the diaphragm slurry was 2 μm, and in the membrane layer formed by the diaphragm slurry, the weight ratio of inorganic particles to dispersant was 30:0.5;

[0281] (3) Preparation of manganese-based lithium batteries.

[0282] Select LiNi 0.5 Mn 1.5 O4 is used as the positive electrode active material to prepare a positive electrode sheet, which is cut by a cutting machine to obtain a positive electrode sheet with a width of 5 cm and a length of 100 cm; graphite is selected as the negative electrode active material to prepare a negative electrode sheet, which is cut by a cutting machine to obtain a negative electrode sheet with a width of 7 cm and a length of 102 cm; the diaphragm prepared in step (2-2) is cut by a cutting machine to obtain a diaphragm with a width of 9 cm and a length of 120 cm; the cut positive electrode sheet, diaphragm and negative electrode sheet are stacked and assembled into a manganese-based lithium battery dry cell, which is then put into a shell, an organic electrolyte is injected, and the cell is sealed to obtain a manganese-based lithium-ion battery, which is then formed, divided and tested for comprehensive electrochemical properties according to conventional industrial processes.

[0283] Example 16

[0284] (1) Type of binder.

[0285] The adhesive is R10 / R20 / R30-CS50-Y14 / Y21 / Y36.

[0286] (2) Preparation of a diaphragm.

[0287] (2-1) Preparation of diaphragm slurry:

[0288] After deionized water and potassium polyacrylate (dispersant) are mixed, a sand mill is used to stir and disperse them at a stirring rate of 600 rpm / min for 20 min; SiO2 inorganic ceramic particles (inorganic particles) with a particle size of 30 nanometers are then added, and a sand mill is used to stir and disperse them at a stirring rate of 5000 rpm / min for 60 min; finally, the binder prepared in step (1) is added, and a magnetic stirring is used to stir and disperse them at a stirring rate of 1000 rpm / min for 60 min to obtain a diaphragm slurry; wherein the viscosity of the diaphragm slurry is 2500 mPa.s;

[0289] (2-2) Preparation of diaphragm

[0290] A PE porous membrane with a thickness of 12 μm and a pore size of 10 nm was selected as the base membrane; the PE porous membrane was placed on a sprayer, and the diaphragm slurry obtained in step (2-1) was evenly coated on both sides of the PE porous membrane, and placed in an oven at 100° C. for 120 min to obtain a diaphragm with a total thickness of 22 μm, wherein the membrane layer formed by the diaphragm slurry was 5 μm, and in the membrane layer formed by the diaphragm slurry, the weight ratio of inorganic particles to dispersant was 35:2;

[0291] (3) Preparation of manganese-based lithium batteries.

[0292] Select LiNi 0.5 Mn 1.5 O4 is used as the positive electrode active material to prepare a positive electrode sheet, which is cut by a cutting machine to obtain a positive electrode sheet with a width of 5 cm and a length of 100 cm; graphite is selected as the negative electrode active material to prepare a negative electrode sheet, which is cut by a cutting machine to obtain a negative electrode sheet with a width of 7 cm and a length of 102 cm; the diaphragm prepared in step (2-2) is cut by a cutting machine to obtain a diaphragm with a width of 9 cm and a length of 120 cm; the cut positive electrode sheet, diaphragm and negative electrode sheet are stacked and assembled into a manganese-based lithium battery dry cell, which is then put into a shell, an organic electrolyte is injected, and the cell is sealed to obtain a manganese-based lithium-ion battery, which is then formed, divided and tested for comprehensive electrochemical properties according to conventional industrial processes.

[0293] Embodiment 17

[0294] (1) Type of binder.

[0295] The adhesive is R10 / R20 / R30-CS50-Y17 / Y20 / Y39.

[0296] (2) Preparation of a diaphragm.

[0297] (2-1) Preparation of diaphragm slurry:

[0298] After deionized water and potassium polyacrylate (dispersant) are mixed, a sand mill is used for stirring and dispersing at a stirring rate of 500 rpm / min for 15 min; LLTO inorganic ceramic particles (inorganic particles) with a particle size of 1 micron are then added, and a sand mill is used for stirring and dispersing at a stirring rate of 2000 rpm / min for 60 min; finally, the binder prepared in step (1) is added, and a magnetic stirring is used for stirring and dispersing at a stirring rate of 2000 rpm / min for 60 min to obtain a diaphragm slurry; wherein the viscosity of the diaphragm slurry is 300 mPa.s;

[0299] (2-2) Preparation of diaphragm

[0300] A PVDF nanofiber porous membrane with a thickness of 40 μm and a pore size of 2 μm is selected as the base membrane; the above-mentioned PVDF nanofiber porous membrane is placed on a knife coating machine, and the diaphragm slurry obtained in step (2-1) is evenly coated on both sides of the PVDF nanofiber porous membrane, and placed in a 50°C oven for drying for 120 minutes to obtain a diaphragm with a total thickness of 42 μm, wherein the membrane layer formed by the diaphragm slurry is 1 μm, and in the membrane layer formed by the diaphragm slurry, the weight ratio of inorganic particles to dispersant is 40:0.1;

[0301] (3) Preparation of manganese-based lithium batteries.

[0302] LiMnPO4 is selected as the positive electrode active material to prepare a positive electrode sheet, which is cut by a cutting machine to obtain a positive electrode sheet with a width of 5 cm and a length of 100 cm; graphite is selected as the negative electrode active material to prepare a negative electrode sheet, which is cut by a cutting machine to obtain a negative electrode sheet with a width of 7 cm and a length of 102 cm; the diaphragm prepared in step (2-2) is cut by a cutting machine to obtain a diaphragm with a width of 9 cm and a length of 120 cm; the cut positive electrode sheet, diaphragm and negative electrode sheet are stacked and assembled into a manganese-based lithium battery dry cell, which is then put into a shell, an organic electrolyte is injected, and the battery is sealed to obtain a manganese-based lithium-ion battery, which is then formed, divided and tested for comprehensive electrochemical performance according to conventional industrial processes.

[0303] Embodiment 18

[0304] The difference between Example 18 and Example 2 is that:

[0305] (1) The adhesive is R10 / R20 / R30-CS50-Y12 / Y24 / Y38.

[0306] Embodiment 19

[0307] The difference between Example 19 and Example 2 is that:

[0308] (1) The adhesive is R10 / R20 / R30-CS50-Y17 / Y25 / Y39.

[0309] Embodiment 20

[0310] The difference between Example 20 and Example 2 is that:

[0311] (1) The adhesive is R10 / R20 / R30-CS50-Y16 / Y29 / Y31.

[0312] Embodiment 21

[0313] The difference between Example 21 and Example 2 is that:

[0314] (1) The adhesive is R10 / R20 / R30-CS50-Y16 / Y21 / Y34.

[0315] Embodiment 22

[0316] The difference between Example 22 and Example 2 is that:

[0317] (1) The adhesive is R11 / R23 / R34-CS25-Y11 / Y24 / Y36.

[0318] Embodiment 23

[0319] The difference between Example 23 and Example 2 is that:

[0320] (1) The adhesive is R10 / R25 / R36-CS25-Y15 / Y27 / Y34.

[0321] Embodiment 24

[0322] The difference between Example 24 and Example 2 is that:

[0323] (1) Types of binders

[0324] The adhesive is R12 / R18 / R29-CS25-Y17 / Y23 / Y39.

[0325] Embodiment 25

[0326] The difference between Example 25 and Example 2 is that:

[0327] (1) The adhesive is R16 / R27 / R39-CS25-Y12 / Y24 / Y33.

[0328] Embodiment 26

[0329] The difference between Example 26 and Example 2 is that:

[0330] (2-2) In the membrane layer formed by the diaphragm slurry, the weight ratio of the inorganic particles to the dispersant is 50:3.

[0331] Embodiment 27

[0332] The difference between Example 27 and Example 2 is that:

[0333] (2-2) In the membrane layer formed by the diaphragm slurry, the weight ratio of the inorganic particles to the dispersant is 25:3.

[0334] Embodiment 28

[0335] The difference between Example 28 and Example 2 is that:

[0336] (2-2) In the membrane layer formed by the diaphragm slurry, the weight ratio of the inorganic particles to the dispersant is 30:0.05.

[0337] Embodiment 29

[0338] The difference between Example 29 and Example 2 is that:

[0339] (1) The adhesive is R10 / R20 / R30-CS4-Y10 / Y20 / Y30.

[0340] Embodiment 30

[0341] The difference between Example 30 and Example 2 is:

[0342] (1) The adhesive is R10 / R20 / R30-CS105-Y10 / Y20 / Y30.

[0343] Comparative Example 1

[0344] The difference between Comparative Example 1 and Example 2 is:

[0345] The binder of Comparative Example 1 is sodium carboxymethyl cellulose (CMC).

[0346] Comparative Example 2

[0347] The difference between Comparative Example 2 and Example 14 is:

[0348] The binder of Comparative Example 2 is sodium carboxymethyl cellulose (CMC).

[0349] Comparative Example 3

[0350] The difference between Comparative Example 3 and Example 15 is:

[0351] The binder of Comparative Example 3 is sodium carboxymethyl cellulose (CMC).

[0352] Comparative Example 4

[0353] The difference between Comparative Example 4 and Example 21 is:

[0354] The binder of Comparative Example 4 is sodium carboxymethyl cellulose (CMC).

[0355] Comparative Example 5

[0356] The difference between Comparative Example 5 and Example 22 is:

[0357] The binder of Comparative Example 5 is sodium carboxymethyl cellulose (CMC).

[0358] Performance Testing

[0359] 1. The weight average molecular weight of the polymer.

[0360] A Waters 2695 Isocratic HPLC gel chromatograph (differential refractive index detector 2141) was used. A polystyrene solution sample with a mass fraction of 3.0% was used as a reference, and a matching chromatographic column was selected (oily: Styragel HT5 DMF7.8×300mm+Styragel HT4). A 3.0% polymer gel solution was prepared with purified N-methylpyrrolidone (NMP) solvent, and the prepared solution was allowed to stand for one day for use. During the test, tetrahydrofuran was first drawn with a syringe and rinsed, and repeated several times. Then 5 ml of the experimental solution was drawn, the air in the syringe was expelled, and the needle tip was wiped dry. Finally, the sample solution was slowly injected into the injection port. Data was obtained after the indication stabilized.

[0361] 2. Manganese content detection.

[0362] Using MY2245CQ01 inductively coupled plasma atomic emission spectrometer (ICP-OSE), hydrochloric acid (1+19) was used to prepare standard solutions of different concentrations of 0 μg / mL, 0.1 μg / mL, 0.25 μg / mL, 0.5 μg / mL, 1 μg / mL, and 1.5 μg / mL. The above solutions were passed through the injector and entered the instrument for testing. The spectral intensity of manganese element was determined and a standard curve was drawn. Weigh the manganese-containing sample of each embodiment and comparative example, place it in a 100mL glass beaker, moisten it with a small amount of water, add 20mL of hydrochloric acid (1+1), cover it with a watch glass, heat it on a heating plate at 300°C in a fume hood to slightly boil for 30min, cool it, filter it with filter paper, wash the filter residue with distilled water for 5 to 7 times, transfer the filtrate and the washing water into a 200mL volumetric flask together, dilute it to the scale with high-grade pure water to obtain a test solution, shake it well, and enter the instrument test through the injector to determine the spectral intensity of the manganese element, and obtain the manganese content concentration on the standard curve.

[0363] 3. Rate performance testing of manganese-based lithium batteries.

[0364] At 55°C, the lithium-ion batteries prepared in the embodiments and comparative examples were charged at a rate of 1C, and discharged at rates of 1C, 2C, and 4C, and discharged at 100% DOD (Depth of Discharge). Each rate charge and discharge cycle was repeated 5 times, and the retention rate of the discharge capacity was recorded. The higher the rate, the better the rate capability.

[0365] 4. High temperature storage capacity retention rate detection of manganese-based lithium batteries.

[0366] At 55°C, the lithium ion batteries prepared in the embodiments and comparative examples were stored in a 55°C constant temperature box, and were charged and discharged at a rate of 1C / 1C after 60 days. The capacity value after discharge was recorded at 100% DOD, and the capacity retention rate was calculated based on the discharge capacity of the lithium ion battery before storage: A1-A2 / A1*100%, where A1 is the 1C / 1C discharge capacity of the lithium ion battery before high temperature storage, and A2 is the 1C / 1C discharge capacity of the lithium ion battery after high temperature storage.

[0367] 5. High temperature cycle life test of manganese-based lithium batteries.

[0368] Cycling performance test method: At 55°C, the lithium-ion batteries prepared in each embodiment and comparative example are charged at a rate of 1C and discharged at a rate of 1C, and continuous cycling tests are performed in the range of 3%-100% SOC (State of Charge) until the capacity of the lithium-ion battery is less than 80% of the initial capacity. The number of cycles is recorded and recorded as the cycle life.

[0369] The important parameters for preparing the binder and the separator are shown in Table 1. The manganese-based lithium batteries of various embodiments and comparative examples were tested, and the test results are shown in Table 2.

[0370] Table 1

[0371]

[0372] Table 2

[0373]

[0374] Table 3

[0375]

[0376] Table 4

[0377]

[0378] According to the data analysis of Table 1 and Table 2:

[0379] Compared with the sodium carboxymethyl cellulose binder used in Comparative Examples 1-5, the binder prepared in Example 1-30 has excellent manganese ion absorption effect, excellent water-soluble bonding effect, excellent ion transmission effect, and excellent mechanical strength. The corresponding manganese-based lithium-ion battery has excellent rate performance, capacity retention rate, cycle life, and excellent safety.

[0380] The binder prepared in Example 1-30 was used to prepare a manganese-based lithium battery, and the manganese-based lithium battery was tested for 200 cycles at 55°C, and the manganese ion content was less than or equal to 1.8ug / mg. In particular, the binder prepared in Example 1-28 was used to prepare a manganese-based lithium battery, and the manganese-based lithium battery was tested for 200 cycles at 55°C, and the manganese ion content was less than 1.38ug / mg; in contrast, the sodium carboxymethyl cellulose binder of Comparative Example 1-5 was used to prepare a manganese-based lithium battery, and the manganese-based lithium battery was tested for 200 cycles at 55°C, and the manganese ion content was greater than 18.9ug / mg. It shows that the binder prepared in the embodiment of the present application has an excellent effect of capturing manganese ions.

[0381] Manganese-based lithium batteries were prepared using the binder prepared in Examples 9-11. Since the binder included lithium ion transport groups, the manganese-based lithium batteries were subjected to 1C, 2C, and 4C rate performance tests (55°C), and the manganese-based lithium batteries had excellent rate performance. In contrast, manganese-based lithium batteries were prepared using the binders of Examples 26, 27, and 28 and Comparative Examples 1-5. Since the binder did not include lithium ion transport groups, the manganese-based lithium batteries were subjected to 1C, 2C, and 4C rate performance tests, and the manganese-based lithium batteries had poor rate performance.

[0382] The manganese-based lithium battery was prepared by using the binder prepared in Example 1-30, and the manganese-based lithium battery was tested for 200 cycles at 55°C, and the capacity retention rate was maintained at a relatively good level. In particular, the manganese-based lithium battery was prepared by using the binder prepared in Example 1-28, and the manganese-based lithium battery was tested for 200 cycles at 55°C, and the capacity retention rate was maintained at a level above 90%. In contrast, the manganese-based lithium battery was prepared by using the sodium carboxymethyl cellulose binder of Comparative Examples 1-5, and the manganese-based lithium battery was tested for 200 cycles at 55°C, and the capacity retention rate was poor.

[0383] The manganese-based lithium battery was prepared by using the binder prepared in Example 1-30. After the manganese-based lithium battery was stored at 55°C for 60 days, the manganese-based lithium battery could maintain a relatively good high-temperature storage performance. In particular, the manganese-based lithium battery was prepared by using the binder prepared in Example 1-28. After the manganese-based lithium battery was stored at 55°C for 60 days, the capacity retention rate of the manganese-based lithium battery reached more than 85%. In contrast, the manganese-based lithium battery was prepared by using the sodium carboxymethyl cellulose binder of Comparative Example 1-5. After the manganese-based lithium battery was stored at 55°C for 60 days, the capacity retention rate of the manganese-based lithium battery was about 50%.

[0384] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A polymer, characterized in that The polymer comprises a main chain polymer and a first branch chain, wherein the main chain polymer comprises a structural unit shown in Formula I, and the first branch chain comprises a chelating agent. Wherein, Y in Formula I represents the bonding position between the main chain polymer and the first branch chain.

2. The polymer according to claim 1, characterized in that The polymer includes a second branch chain, the second branch chain includes an active group, and the active group is used to increase the steric hindrance of the polymer. The main chain polymer includes a first main chain polymer, and the first main chain polymer includes a structural unit shown in Formula II. Wherein, R in Formula II represents the bonding position between the first main chain polymer and the second branch chain.

3. The polymer according to claim 2, characterized in that The polymer includes a plurality of different first branches, the main chain polymer includes a second main chain polymer, and the second main chain polymer includes a structural unit shown in formula III, Wherein, Y1, Y2, and Y3 in Formula III represent the bonding positions of the second main chain polymer and a plurality of different first side chains.

4. The polymer according to claim 3, characterized in that The polymer includes a plurality of different second branches, the main chain polymer includes a third main chain polymer, and the third main chain polymer includes a structural unit shown in Formula IV, Wherein, R1, R2, and R3 in Formula IV represent the bonding positions of the third main chain polymer and a plurality of different second branch chains.

5. The polymer according to any one of claims 1 to 4, characterized in that The chelating agent includes At least one of .

6. The polymer according to any one of claims 2 to 4, characterized in that The active groups include At least one of .

7. The polymer according to claim 6, characterized in that The active groups include At least one of .

8. The polymer according to any one of claims 1 to 4, characterized in that The polymer further includes a polar group, and the polar group is bonded to the main chain polymer.

9. The polymer according to any one of claims 1 to 4, characterized in that The number of repetitions of the structural unit represented by formula I of the main chain polymer is 15 to 300.

10. The polymer according to any one of claims 1 to 4, characterized in that The weight average molecular weight of the polymer is 400,000 to 1,000,000.

11. A method for preparing the polymer according to any one of claims 1 to 10, characterized in that: include: In an aqueous solvent, subjecting a first polymer, an amidating agent, and a chelating agent to an amidation reaction to obtain a polymer; Wherein, the first polymer comprises a structural unit as shown in the following formula V:

12. The method according to claim 11, characterized in that Before the amidation reaction, the first polymer and the alkylating agent are subjected to an alkylation reaction.

13. The method according to claim 11, characterized in that Before the amidation reaction, the first polymer and the carboxylation agent are subjected to a carboxylation reaction.

14. A binder, characterized in that: The binder comprises the polymer described in any one of claims 1 to 10, or the polymer prepared by the method described in any one of claims 11 to 13.

15. A diaphragm, characterized in that: It comprises a base film and a film layer arranged on at least one surface of the base film, wherein the film layer comprises inorganic particles and the binder according to claim 14.

16. The diaphragm according to claim 15, characterized in that The mass fraction of the binder in the separator is 0.01% to 10%.

17. A manganese-based lithium battery, characterized in that: The diaphragm according to claim 15 or 16.

18. A vehicle, characterized in that: Including the manganese-based lithium battery as described in claim 17.

Citation Information

Cited By

  • Manganese-based lithium battery, preparation method thereof and power utilization device comprising manganese-based lithium battery

    CN120545363A